2014
DOI: 10.1002/bies.201400100
|View full text |Cite
|
Sign up to set email alerts
|

Microbial gardening in the ocean's twilight zone: Detritivorous metazoans benefit from fragmenting, rather than ingesting, sinking detritus

Abstract: Sinking organic particles transfer ∼10 gigatonnes of carbon into the deep ocean each year, keeping the atmospheric CO2 concentration significantly lower than would otherwise be the case. The exact size of this effect is strongly influenced by biological activity in the ocean's twilight zone (∼50–1,000 m beneath the surface). Recent work suggests that the resident zooplankton fragment, rather than ingest, the majority of encountered organic particles, thereby stimulating bacterial proliferation and the deep-oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 51 publications
3
99
0
Order By: Relevance
“…This new scenario of trophic pathways is not commonly found in the literature, as very little is known about pelagic detritivory. It has been proposed that zooplankton ingestion of detritus breaks up marine snow particles, facilitating bacterial degradation that, in turn, increases the nutritional value of the organic matter (Mayor et al, 2014). Although these authors focus their hypothesis on the water column below the euphotic zone, similar processes could occur in the mixed layer.…”
Section: Discussionmentioning
confidence: 99%
“…This new scenario of trophic pathways is not commonly found in the literature, as very little is known about pelagic detritivory. It has been proposed that zooplankton ingestion of detritus breaks up marine snow particles, facilitating bacterial degradation that, in turn, increases the nutritional value of the organic matter (Mayor et al, 2014). Although these authors focus their hypothesis on the water column below the euphotic zone, similar processes could occur in the mixed layer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their decomposition is not a simple process, but there is no evidence of longterm accumulation of those substrates in aquatic ecosystems (Gooday 1990). This suggests complex and efficient degradation pathways involving a number of interactions (Mayor et al 2014), as demonstrated in decomposing wood (Borsodi et al 2005), sediments (Cardenas et al 2008), wetlands (Ibekwe et al 2003), and bioreactors (Hiibel et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Close interactions between metazoan consumers and microzooplankton have been proposed as "gardening by metazoans" through fragmenting detrital particles, promoting microbial populations (Mayor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%